Trabalho forçado e trabalho escravo no Brasil: diferença conceitual e busca da eficácia em seu combate - Cruz, Claudia Ferreira (2013)
This thesis approached a relatively complex phenomenon that is still observed in the Brazilian society: the existence of slave labor and forced labor, both in rural and urban areas. The main objective was to bring elements trying to show the conceptual differences between both, as well as to propose subsidies to eradicate these conditions, despite of conceptual aspects, wrong treatment even in the public sphere -, ideological positions or even lack of clarity in the definition of each of these concepts. Seeking to achieve this goal, this thesis is structured as follows: it began with a historical review of slave labor in Brazil and worldwide; then, it described what has happened on the international scene in terms of slave labor and forced labor; after that, it included features of both, considering their differences nowadays and highlighting the importance of the fundamental rights in the understanding of this differentiation. In order to deep this discussion, this work brought up the case of Bolivian immigrants in São Paulo, where it seems difficult to say exactly what it is: forced labor or slave labor? Then became involved in the revision of Brazilian legislation about the subject, showed the position of the leading Brazilian institutions involved in the solution of the exploitation of human labor, after revealing the extent of this problem in the Brazilian case. Finally, based on this material, realized several of recommendations, suggestions and subsidies to expand and improve the fight against forced labor and slave labor in Brazil, whether in rural or urban areas. Among these, are stand out: the discipline of terminology and standard of sentences in the sphere of the labor court; the complement of the PEC in terms of clarity about what is slave labor, using the concept of Decent Work for easier differentiation of terms; setting up recommendations to make clear and consensual what is slave labor and forced labor. The final conclusions bring the key messages that emerged from the development of the thesis: persisting on the fight against the exploitation of human labor in all its forms; taking out the ideological character of the discussion; regulating the outsourcing; the need of clearly identify the phenomenon: criminal problem or circumventing the labor laws?; understand them as an economic phenomenon, indicating the need of prevention and not just combat, and the absolute necessity of a clear concept of what the slave labor is